Analysis Of The Need And Demand For Health Services At The Marsabut Lake Health Center, South Tapanuli Regency In The Jkn Era - Normayanti Rambe (Institute of Computer Science (IOCS), 2022)
The phenomenon of people preferring to seek treatment abroad instead of using domestic health services is a big challenge. This challenge can be answered by improving quality in all fields, especially the health sector. So, this is what will help health service providers in setting strategies to meet the needs of the community in the health sector. The purpose of the study was to determine the need, demand, and utility of public health services in the work area of the Marsabut Lake Health Center, South Tapanuli Regency. Types of quantitative research with a cross-sectional approach. The population is a community living in the working area of Lake Marsabut, South Tapanuli Regency. With a sample number of 60 people. The study was conducted in June 2022. The results of research related to need showed that the main needs of respondents related to health service facilities were quality and distance ≤ 3 km. Community demand is dental poly and general poly services provided by Marsabut Lake, South Tapanuli Regency.